Venezuelan Higher Education’s Legacy Under Cha´vez - Albornoz, Orlando (International Higher Education, 2013)
Government and universities. The impact of the Chavez regime on higher education in Venezuela has been substantial. In general, higher education has been weakened and is more subject to governmental control.